A change in temporal organization of fidgety movements during the fidgety movement period is common among high risk infants. (July 2016) - Sæther, Rannei; Støen, Ragnhild; Vik, Torstein; Fjørtoft, Toril; Vågen, Randi Tynes; Silberg, Inger Elisabeth; Loennecken, Marianne; Møinichen, Unn Inger; Lydersen, Stian; Adde, Lars
Abstract: Aim: General movement assessment (GMA) at 9–20 weeks post-term, can effectively predict cerebral palsy. Our aim was to evaluate intra-individual variability of the temporal organization of fidgety movements (FMs) in high risk infants. Material and methods: 104 High risk infants (66 males) with at least two video recordings from the FMs period participated. 45 of the infants had GA <28 weeks and/or BW ≤800 g. Mean post-term age at first and second assessments was 11.0 (8–16) and 14.0 (11–17) weeks, respectively, and median time-difference between the assessments was 2.0 (range: three days to six weeks) weeks. Video recordings were analyzed according to Prechtl's GMA. Results: 33 (32%) Infants were classified differently at first and second assessments. Six infants (6%) changed from normal to abnormal, and 10 (10%) changed from abnormal to normal FMs. Seven of the ten who changed classification from abnormal to normal were born before GA 26 weeks. A change between intermittent and continual, which are both considered normal, was observed in 17 (16%) infants. Conclusion: A change in temporal organization of FMs is common in high risk infants. Especially in extremely preterm infants with abnormal FMs, more than one assessment should be performed before long-term prognosis is considered. Highlights: A change in temporal organization of FMs is common in high risk infants. Especially in extremely preterm infants with abnormal FMs. More than one assessment should be performed before long-term prognosis is considered.